ANALISIS LAYANAN BIMBINGAN DAN KONSELING TENTANG POTENSI DIRI PADA PESERTA DIDIK KELAS XI SMA NEGERI 6 PONTIANAK - Nurhasanah, Nurhasanah; Endang, Busri; Lestari, Sri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis study is analysis of guidance and counselling about self potential in classroom students XI SMA Negeri 6 Pontianak. The problem of this research is how is the service guidance and counselling about self potential in classroom students XI SMA Negeri 6 Pontianak.This study aims to analyze is the service guidance and counselling about self potential in classroom students XI SMA Negeri 6 Pontianak. Metode used is descriptive method and the form of research is a survey research. The population in this study as many as 262 and as many samples 68 students class XI SMA Negeri 6 Pontianak. This research uses quantitative approach. Data collection techniques used are indirect communication techniques in the form of questionnaires, direct communication in the form of interviews, and documentation study techniques in the form of documentation. While the technique of data analysis using the formula percentage.Based on the results of this study understanding of self potential potential in classroom students XI SMA Negeri 6 Pontianak. reached a score of 83,27% with the category of